2020
DOI: 10.22456/2175-2745.91414
|View full text |Cite
|
Sign up to set email alerts
|

Group Labeling Methodology Using Distance-based Data Grouping Algorithms

Abstract: Clustering algorithms are often used to form groups based on the similarity of their members. In this context, understanding a group is just as important as its composition. Identifying, or labeling groups can assist with their interpretation and, consequently, guide decision-making efforts by taking into account the features from each group. Interpreting groups can be beneficial when it is necessary to know what makes an element a part of a given group, what are the main features of a group, and what are the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…The Table XIV displays the result of labeling the method of [20] for the Iris dataset. It was observed that the result was generated after 568 iterations of the method based on degrees of membership, which corresponds to a very high computational cost, in addition to having 12 database elements that could not be labeled.…”
Section: A Iris Datasetmentioning
confidence: 99%
See 2 more Smart Citations
“…The Table XIV displays the result of labeling the method of [20] for the Iris dataset. It was observed that the result was generated after 568 iterations of the method based on degrees of membership, which corresponds to a very high computational cost, in addition to having 12 database elements that could not be labeled.…”
Section: A Iris Datasetmentioning
confidence: 99%
“…This model, proposed in this research, generated a maximum of six iterations to form labels, corroborating and reducing the computational effort. No criteria were used to infer the optimal number of groups in [20], so the author used K=3 for clustering. In this proposed model, it was observed that the computational cost spent on forming the labels was extremely low, favoring a minimum number of iterations, compared to the [20] model, which presented a lower rate than this research model.…”
Section: A Iris Datasetmentioning
confidence: 99%
See 1 more Smart Citation